Testing the Developmental Origins of Health and Disease Hypothesis for Psychopathology Using Family‐Based, Quasi‐Experimental Designs. (16th July 2014) - Donofrio, Brian; Class, Quetzal; Lahey, Benjamin; Larsson, Henrik
Abstract The Developmental Origin of Health and Disease (DOHaD) hypothesis is a broad theoretical framework that emphasizes how early risk factors causally influence psychopathology. Researchers have raised concerns about the causal interpretation of statistical associations between early risk factors and later psychopathology because most studies have been unable to rule out the possibility of environmental and genetic confounding. In this article, we illustrate how family‐based, quasi‐experimental designs can test the DOHaD hypothesis by ruling out alternative hypotheses. We review the logic underlying sibling‐comparison, cotwin control, offspring of siblings/twins, adoption, and in vitro fertilization designs. We then present results from studies using these designs focused on broad indices of fetal development (low birth weight and gestational age) and a particular teratogen, smoking during pregnancy. The results provide mixed support for the DOHaD hypothesis for psychopathology, illustrating the critical need to use designs that rule out unmeasured confounding.